Mitigasi Green Skepticism pada Konsumen Kopi Spesialti di Manado: Peran Multidimensi Transparansi Rantai Pasok dengan Mediasi Perceived Brand Authenticity - Fitayantri Tamau; Injilia Wulan Gratia Wua; Lidya Djuwita Pratiwi Canon (ITB AAS Indonesia Surakarta, 2026)
Abstract This study aims to investigate the mitigation mechanism of Green Skepticism among specialty coffee consumers in Manado City by positioning supply chain transparency as a multidimensional variable mediated by Perceived Brand Authenticity. The research method used is quantitative explanatory with a survey technique. Data were collected from 150 respondents selected using purposive sampling with the criteria of active consumers of specialty coffee in Manado. Data analysis was performed using the Partial Least Square - Structural Equation Modeling (PLS-SEM) approach. The results showed that supply chain transparency directly had no significant effect on reducing skepticism. However, transparency has a significant positive effect on perceived brand authenticity. The main finding of this study confirms the role of full mediation of brand authenticity; transparency is only effective in reducing skepticism if it successfully builds a perception of authenticity first. Practical implications suggest coffee business owners use storytelling in presenting transparency data to build emotional trust.